Artificial Intelligence Applications and Innovations AIAI 2012 International Workshops: AIAB, AIeIA, CISE, COPA, IIVC, ISQL, MHDW, and WADTMB, Halkidiki, Greece, September 27-30, 2012, Proceedings, Part II - Iliadis, Lazaros; Maglogiannis, Ilias; Papadopoulos, Harris; Karatzas, Kostas; Sioutas, Spyros; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the Workshops held at the 8th IFIP WG 12.5 International Conference on Artificial Intelligence Applications and Innovations, AIAI 2012, in Halkidiki, Greece, in September 2012. The book includes a total of 66 interesting and innovative research papers from the following 8 workshops: the Second Artificial Intelligence Applications in Biomedicine Workshop (AIAB 2012), the First AI in Education Workshop: Innovations and Applications (AIeIA 2012), the Second International Workshop on Computational Intelligence in Software Engineering (CISE 2012), the First Conformal Prediction and Its Applications Workshop (COPA 2012), the First Intelligent Innovative Ways for Video-to-Video Communiccation in Modern Smart Cities Workshop (IIVC 2012), the Third Intelligent Systems for Quality of Life Information Services Workshop (ISQL 2012), the First Mining Humanistic Data Workshop (MHDW 2012), and the First Workshop on Algorithms for Data and Text Mining in Bioinformatics (WADTMB 2012).
Future SDP through Cloud Architectures -- Detection of Geriatric Depression Symptoms Co-existing with Cognitive Decline -- Combining Outlier Detection with Random Walker for Automatic Brain Tumor Segmentation -- An Ontological Approach for Domain Knowledge Modeling and Management in E-Learning Systems -- Association Rules Mining from the Educational Data of ESOG Web-Based Application -- Adaptation Strategies: A Comparison between E-Learning and E-Commerce Techniques -- Player Modeling Using HOSVD towards Dynamic Difficulty Adjustment in Videogames -- Proposing a Fuzzy Adaptation Mechanism Based on Cognitive Factors of Users for Web Personalization -- Computational Intelligence for User and Data Classification in Hospital Software Development -- Application of Conformal Prediction in QSAR -- Online Cluster Approximation via Inequality -- Reliable Probability Estimates Based on Support Vector Machines for Large Multiclass Datasets -- LiveCity: A Secure Live Video-to-Video Interactive City Infrastructure -- Enhancing Education and Learning Capabilities via the Implementation of Video-to-Video Communications -- Developing Innovative Live Video-to-Video Communications for Smarter European Cities -- Utilizing a High Definition Live Video Platform to Facilitate Public Service -- Low Power and Bluetooth-Based Wireless Sensor Network for Environmental Sensing Using Smartphones -- Making Sense of Sensor Data Using Ontology: A Discussion for Residential Building Monitoring -- Success Is Hidden in the Students$1 (BData -- Web Mining to Create Semantic Content: A Case Study for the Environment -- Mood Classification Using Lyrics and Audio: A Case-Study in Greek Music -- Multi-genome Core Pathway Identification through Gene Clustering -- On Topic Categorization of PubMed Query Results -- Using an Atlas-Based Approach in the Analysis of Gene Expression Maps Obtained by Voxelation -- Parallel Implementation of the Wu-Manber Algorithm Using the OpenCL Framework.s
Keywords: Computer science; Data mining; Artificial intelligence; Computer vision; Optical pattern recognition; Education; Computer Science; Artificial Intelligence (incl. Robotics).; Pattern Recognition; Data Mining and Knowledge Discovery; Image Processing and Computer Vision; Computers and Education; Information Systems Applications (incl. Internet).